K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 7 2023

\(D=\left(2x+1\right)^2-\left(2x-3\right)^2+6x\)

\(D=\left(4x^2+4x+1\right)-\left(4x^2-12x+9\right)+6x\)

\(D=\left(4x^2-4x^2\right)+\left(4x-12x+6x\right)+\left(1-9\right)\)

\(D=-2x-8\)

_______________________

\(E=\left(x-4\right)^2-x\left(x+2\right)-2x+3\)

\(E=\left(x^2-8x+16\right)-\left(x^2+2x\right)-2x+3\)

\(E=\left(x^2-x^2\right)-\left(8x+2x+2x\right)+\left(16+3\right)\)

\(E=-12x+19\)

Đánh lẽ phải bỏ dấu ngoặc và đổi dấu chứ nhỉ??